Pengaruh Lokasi dan Atmosphere Store Terhadap Keputusan Pembelian pada Toko Dillaa - Putri Indah Lestari; Muhajirin Muhajirin (Jurnal Serambi Ekonomi dan Bisnis, 2023)
Purchasing decisions are important for a business, therefore business people have an obligation to pay attention to the factors that influence consumer purchasing decisions. This study aims to determine and analyze the effect of location and store atmosphere on purchasing decisions at Toko Dilla. This type of research is associative. The research instrument used was a Likert scale questionnaire. The population used in this research is all consumers who have shopped at the Dilla Store, the exact number of which is not known. The sample in this study was 96 people who had shopped at Toko Dilla, with the sampling technique used was purposive sampling technique. Data was collected by means of observation, questionnaires and literature study. Data analysis techniques use validity tests, reliability tests, classical assumption tests, multiple linear regression, correlation coefficients, determination tests, t tests and f tests. The results showed that the location and atmosphere of the store had a significant effect on purchasing decisions at Dilla Stores.